Peran Kepuasan Kerja Sebagai Mediator Pengaruh Kompensasi dan Beban Kerja Terhadap Kinerja - Yogi Noviansyah, Kafita; Prima Rini, Hesty; Evanthi, Ayundha (Jurnal Riset Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of compensation and workload on employee performance through job satisfaction at PO Bus PT. X. The research employs a quantitative method involving 40 employees working as Drivers and Co-Drivers, with data analyzed using SEM-PLS version 4.0. The results indicate that compensation has a positive and significant effect on performance, both directly and indirectly through job satisfaction. Conversely, workload has a negative and significant impact on performance, also both directly and indirectly through job satisfaction. These findings are expected to help the company address employee-related issues in order to optimize performance.